DEVELOPMENT OF 2-13-YEAR-OLD VOLLEYBALL PLAYERS PASSING THE BALL TECHNIQUE FROM ABOVE BY ACTION GAMES - M.S Ramazonova (TADQIQOTLAR, 2025)
Abstract: The goal is to study the technique of passing the ball from the top with two hands for 12-13-year-old volleyball players and to develop it rapidly with the help of selected action games. At the initial stage of training in sports technique, the issues of  using  mobile games  were  conducted  on the  example  of  young volleyball players.  In  the  study,  special  exercises  and  action  games  aimed  at  forming  the technique of receiving and passing the ball with two hands from above in 12-13-year-old volleyball players engaged in the initial training stage were selected based on the research.